2023
DOI: 10.1200/op.22.00668
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Frailty on Health Care Resource Utilization and Costs of Care in Myelodysplastic Syndromes

Abstract: PURPOSE: The role of frailty in affecting survival in myelodysplastic syndromes (MDS) is increasingly recognized. Despite this, a paucity of data exists on the association between frailty and other clinically meaningful outcomes including health care resource utilization and costs of care. METHODS: We linked the Ontario subset of the prospective Canadian MDS registry (including baseline patient/disease characteristics) to population-based health system administrative databases. Baseline frailty was calculated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 46 publications
2
0
0
Order By: Relevance
“…A significant proportion of MDS patients, more than the controls, reported moderate/severe problems in the dimensions of pain/discomfort (49.5%), mobility (41.0%), anxiety/depression (37.9%), and usual activities (36.1%). Other investigators have reported similar data, specifying fatigue and transfusion-dependence as QoL-related symptoms in this patient population [ 10 , 17 , 33 , 34 ]. Impaired QoL imposes an economic burden as well [ 33 ].…”
Section: Discussionsupporting
confidence: 76%
See 1 more Smart Citation
“…A significant proportion of MDS patients, more than the controls, reported moderate/severe problems in the dimensions of pain/discomfort (49.5%), mobility (41.0%), anxiety/depression (37.9%), and usual activities (36.1%). Other investigators have reported similar data, specifying fatigue and transfusion-dependence as QoL-related symptoms in this patient population [ 10 , 17 , 33 , 34 ]. Impaired QoL imposes an economic burden as well [ 33 ].…”
Section: Discussionsupporting
confidence: 76%
“…Other investigators have reported similar data, specifying fatigue and transfusion-dependence as QoL-related symptoms in this patient population [ 10 , 17 , 33 , 34 ]. Impaired QoL imposes an economic burden as well [ 33 ].…”
Section: Discussionsupporting
confidence: 76%